Rehabilitation strategies and neurological consequences in patients with COVID-19: part II - Cetisli-Korkmaz, Nilufer; Bilek, Furkan; Can-Akman, Tuba; Baskan, Emre; Keser, Ilke; Dogru-Huzmeli, Esra; Kilinc, Buse (Taylor & Francis Ltd, 2021)
Background: The 2019 novel coronavirus disease (COVID-19) pandemic has triggered a devastating effect worldwide. Objectives: This review of rehabilitation strategies and neurological consequences in patients with COVID-19 sought to consider potential neurorehabilitation strategies for managing the emerging neurological consequences of COVID-19. Methods: An exploratory review was conducted that comprised a narrative synthesis in two parts. Part I focused on neurological consequences and physiotherapy and rehabilitation approaches. Part II focused on general principles of rehabilitation interventions and precautions that should be considered. Literature on the use of neurorehabilitation approaches was also included in the review. Results: Rehabilitation should be initiated as quickly as possible. Neurorehabilitation protocols include public health training valid for the whole community and providing intensive care, pulmonary rehabilitation, mobilization, exercise and strengthening, whole-body vibration, neuromuscular electrical stimulation, telerehabilitation, and other rehabilitation interventions. Interventions should be conducted while correctly implementing personal protective equipment (PPE), hand hygiene, sterilization procedures, and other precautions to avoid the risk of contamination. Conclusions: Multidimensional assessment should be followed by development of individualized and progressive treatment and neurorehabilitation plans. These plans should focus on existing potential and recovery of mobility and function in particular. It is important for rehabilitation teams to keep gathering and reporting data on patients with COVID-19 and the neurologic complications of COVID-19 during and after the pandemic.
Keywords: COVID-19; neurological consequences; physiotherapy and rehabilitation; neurorehabilitation; exercise; telerehabilitation